Peak pursuits : the emergence of mountaineering in the nineteenth century - Schaumann, Caroline (Yale University Press, 2020)
European forays to mountain summits began in the late eighteenth and early nineteenth centuries with the search for plants and minerals and the study of geology and glaciers. Yet scientists were soon captivated by the enterprise of climbing itself, enthralled with the views and the prospect of "conquering" alpine summits. Mountains inspired Romantic idealizations of nature and became a refuge from the industrializing West. As increased leisure time and advances in infrastructure and equipment opened up once formidable mountain regions to those seeking adventure and sport, a new model of masculinity emerged that was fraught with tensions. This book examines how written and artistic depictions of nineteenth-century exploration and mountaineering in the Andes, the Alps, and the Sierra Nevada shaped cultural understandings of nature and wilderness.